If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 2 = -7 + 2x + 17 Reorder the terms: 2 + 6x = -7 + 2x + 17 Reorder the terms: 2 + 6x = -7 + 17 + 2x Combine like terms: -7 + 17 = 10 2 + 6x = 10 + 2x Solving 2 + 6x = 10 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 2 + 6x + -2x = 10 + 2x + -2x Combine like terms: 6x + -2x = 4x 2 + 4x = 10 + 2x + -2x Combine like terms: 2x + -2x = 0 2 + 4x = 10 + 0 2 + 4x = 10 Add '-2' to each side of the equation. 2 + -2 + 4x = 10 + -2 Combine like terms: 2 + -2 = 0 0 + 4x = 10 + -2 4x = 10 + -2 Combine like terms: 10 + -2 = 8 4x = 8 Divide each side by '4'. x = 2 Simplifying x = 2
| q-17/1=-2 | | 7x-17t+2x=2-8x+15 | | -x+10=12 | | -11s+2s=9 | | 6*x=12 | | k^2-10k+24= | | 2(3n+2)=7(4n+9)+4 | | 11x-9=4x+68 | | -12c+16c=-12 | | 80=5(5n-4) | | v+7/2=3 | | 3y+5y=13 | | 4x+7=3+2x+22 | | -3m^2+16=-284 | | 10k-6=-156 | | -2(x+2)-3(x+6)=-22 | | 4x^2+81=17 | | 3x=15x^2 | | (5x^2)-(6x)-(2)=0 | | x(-4)=8 | | -7(-3x+3)=-105 | | (-5)*x=1/2 | | -2(n-3)=-4 | | 9(x+7)=81 | | x*3/8=-2 | | 3h-h=12 | | 5(x+9)+5=50 | | 3x^2-4x=11 | | 4z+2(z-1)=1-2(z-1) | | 3*(-1/8)=2-x | | 2x-8x-10=-6x+7-10 | | 3(x-2)-5=6x-3(5+x) |